2015
DOI: 10.1186/s40657-015-0017-y
|View full text |Cite
|
Sign up to set email alerts
|

Brain size and urbanization in birds

Abstract: Background: Brain size may affect the probability of invasion of urban habitats if a relatively larger brain entails superior ability to adapt to novel environments. However, once urbanized urban environments may provide poor quality food that has negative consequences for normal brain development resulting in an excess of individuals with small brains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
(47 reference statements)
0
20
3
Order By: Relevance
“…Sol et al (2012) also showed a significant effect of brain size, while Maklakov et al (2011) showed that families of birds with larger brains were more likely to have species that successfully became established in urban areas. Here, we failed to replicate such an effect, as did Møller and Erritzøe (2015) in a much larger study of brain size in urban and rural populations of the same species, and in an independent study of brain size in urban and rural species of birds.…”
Section: Discussioncontrasting
confidence: 79%
“…Sol et al (2012) also showed a significant effect of brain size, while Maklakov et al (2011) showed that families of birds with larger brains were more likely to have species that successfully became established in urban areas. Here, we failed to replicate such an effect, as did Møller and Erritzøe (2015) in a much larger study of brain size in urban and rural populations of the same species, and in an independent study of brain size in urban and rural species of birds.…”
Section: Discussioncontrasting
confidence: 79%
“…Some other studies have shown little evidence that urban‐tolerant species have large residual brain size (Kark et al , Evans et al ), but we found it was highly correlated with urban‐tolerance (Fig. 4, 5; Møller , Maklakov et al , Møller and Erritzøe ). Some studies have found little evidence that urban‐tolerant species have large residual brain size (Kark et al , Evans et al ), but we found it was highly correlated with urban‐tolerance (Fig.…”
Section: Discussioncontrasting
confidence: 46%
“…Despite the breadth of research which has focused on ecological and life history traits associated with urbanization in birds, the results are severely mixed and frequently contradictory. For example, residual brain size in birds is sometimes positively associated with urbanization (Maklakov et al , Møller and Erritzøe ) and sometimes not (Kark et al , Evans et al ). Similarly, contrasting results have been reported for annual fecundity (Croci et al , Møller , Evans et al ) and niche breadth (Kark et al , Evans et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive analysis of birds breeding across Great Britain indicated a primary role of foraging niche position and nest site choice in the process of adaptation to urban life (Evans et al ), while other studies linked urban colonization success to sociality and migratory ability (Chace and Walsh , Kark et al ). Urban invasiveness has also been associated with such traits as innovativeness and behavioural flexibility (Tryjanowski et al , ) or relative brain size (Carrete and Tella ), although the latter relationship is still being debated (Kark et al , Møller and Erritzøe ). While certain phenotypic characteristics may predispose birds to become urban dwellers, the process of urbanization may also provoke further divergence between rural and urban conspecifics in a number of morphological, physiological and behavioural traits (Partecke et al ).…”
mentioning
confidence: 99%